Politics in a changing world : a comparative introduction to political science - Ethridge, Marcus E.; Handelman, Howard , 1943- (Wadsworth, Cengage Learning, 2013)
Providing a foundation for a comparative understanding of political life, POLITICS IN A CHANGING WORLD includes in-depth chapters on political science concepts (ideology, political culture, interest groups, governmental institutions, parties) followed by a series of brief country studies. The concepts and country studies help students acquire a better understanding of the actors and institutions that play a part in diverse political systems, how and why they act in relation to one another, and what their actions mean for the political system and its citizens. The Sixth Edition is thoroughly updated throughout, including coverage of the global economic crisis, the 2010 midterm elections in the US, the Conservative Party-Liberal Democratic Party coalition and the victory of a new Conservative Prime Minister in Great Britain, and the democratic upheavals in Egypt and elsewhere in the Arab world